The Impact of Transformational Leadership on Supporting Organizational Creativity: A Case Study of Employees at Al-Ammari Company in Jeddah (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to identify the impact of transformational leadership in supporting organizational creativity among employees at Al-Ammari Company in Jeddah Governorate. It also provides a scientific contribution to the field of transformational leadership and organizational creativity by linking the theoretical dimensions of transformational leadership (idealized influence, inspirational motivation, individual consideration, and intellectual stimulation) to organizational creativity within the Saudi workplace. It also provides practical recommendations to assist management in adopting inspiring leadership models that restore vitality to the workplace and stimulate organizational renewal and excellence, in line with the aspirations of Vision 2030. The study relied on the descriptive-analytical approach, using a questionnaire as the primary tool for data collection, with data analyzed statistically using SPSS. The study sample was selected using a simple random sample from the company's employee community. The study results demonstrated that transformational leadership is a key factor in enhancing organizational creativity, as a strong, positive correlation was found between the dimensions of transformational leadership and the level of creativity within the organization. The researchers indicated that the level of support for institutional creativity is high, indicating the availability of a work environment that encourages innovation, allowing employees to express and implement their ideas and suggestions, contributing to improving work quality and enhancing institutional performance. The results also revealed that transformational leadership explains 73.1% of the change in the level of institutional creativity, a high percentage that reflects the significant impact of this leadership style. Statistical analysis confirmed that all dimensions of transformational leadership have a statistically significant impact on enhancing institutional creativity.
Keywords: Transformational Leadership; Organizational Creativity; Work Environment